Multiculturalism and religious identity: Canada and India - Sikka, Sonia; Beaman, Lori G. (McGill-Queen's University Press, 2014)
How, and to what extent, can religion be included within commitments to multiculturalism? Multiculturalism and Religious Identity addresses this question by examining the political recognition and management of religious identity in Canada and India. In multicultural policy, practice, and literature, religion has until recently not been included within broader discussions of multiculturalism, perhaps due to worries of potential for conflict with secularism. This collection undertakes a contemporary analysis of how the Canadian and Indian states each approach religious diversity through social and political policies, as well as how religion and secularism meet both philosophically and politically in contested public space. Although Canada and India have differing political and religious histories - leading to different articulations of multiculturalism, religious diversity, and secularism - both countries share a commitment to ensuring fair treatment for the different religious communities they include. Combining broader theoretical and normative reflections with close case studies, Multiculturalism and Religious Identity leads the way to addressing these timely issues in the Canadian and Indian contexts. --Provided by publisher